Test-Retest Reliability of a Questionnaire on Motives for Physical Activity among Adolescents - Kopcakova, Jaroslava; Dankulincova Veselska, Zuzana; Kalman, Michal; Filakovska Bobakova, Daniela; Sigmundova, Dagmar; Madarasova Geckova, Andrea; Klein, Daniel; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of environmental research and public health, 2020)
The aim of this study was to investigate the test-retest reliability of the motives for undertaking physical activity (PA) items from the Health Behavior in School-Aged Children (HBSC) study questionnaire among Slovak and Czech adolescents and to determine whether this reliability differs by gender, age group and country. We obtained data from 580 students aged 11 and 15 years old (51.2% boys) who participated in a test and retest study with a four-week interval in 2013 via the Health Behavior in School-Aged Children cross-sectional study in the Czech Republic and Slovakia. We estimated the test-retest reliability of all 13 dichotomized motives by using Intraclass Correlation Coefficients (ICC) and Cohen's Kappa statistics, for continuous and dichotomized motives, respectively. Test-retest reliability showed moderate agreement for nine motives (ICC from 0.41 to 0.60) and fair agreement for four motives (ICC from 0.33 to 0.40). Kappa statistics were similarly moderate to large (0.33 to 0.61), except for three motives with small or trivial correlations. The motives "To improve my health" and "To enjoy the feeling of using my body" had consistently low Kappas and correlations. Overall, the results of this study suggest that most questions on motives for PA on the HBSC questionnaire have acceptable test-retest characteristics for use among adolescents.
Keywords: Surveys and Questionnaires; Health Behavior in School-Aged Children (HBSC) study; Humans; dítě; Child; Female; lidé; motivation; active living; Slovakia; Slovenská republika; reprodukovatelnost výsledků; adolescence; průzkumy a dotazníky; ženské pohlaví; Male; Reproducibility of Results; Adolescent; Psychometrics; health-related behavior; Czech Republic; Cross-Sectional Studies; Exercise; Česká republika; mužské pohlaví; cvičení; psychometrie; gender; průřezové studie; mladiství